2020
DOI: 10.18196/jmmr.91113
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Attitude in the Handling of Diarrhea in Infant

Abstract: Diarrhea According to epidemiological theory is influenced by 3 factors, namely host, Agent and environment. The host is a landlady or as it is occupied for instance age, nutritional status. Diarrhoea disease in infants whose nutritional status is bad is more difficult to heal because of the damaged intestinal mucosa in the process of a longer revitelization. From the Government Health Service data of Jember District, in May 2008 the number of Diarrhea suffered reaches 4,601. In January 2008, the number of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 2 publications
(3 reference statements)
0
4
1
5
Order By: Relevance
“…In contrast, a study in a village in Indonesia revealed that about 77% of the mothers had a positive attitude toward treating diarrhea [46]. Continuous fluid administration, breastfeeding and using ORS after each diarrhea are very important to replace the lost fluids and minerals in the body [47].…”
Section: Mothers Attitudes Toward Prevention and Management Of Diarrhea Of Their Childrenmentioning
confidence: 99%
“…In contrast, a study in a village in Indonesia revealed that about 77% of the mothers had a positive attitude toward treating diarrhea [46]. Continuous fluid administration, breastfeeding and using ORS after each diarrhea are very important to replace the lost fluids and minerals in the body [47].…”
Section: Mothers Attitudes Toward Prevention and Management Of Diarrhea Of Their Childrenmentioning
confidence: 99%
“…Apabila saat hamil ibu mengalami peningkatan berat badan, maka berat badan pada bayi yang dilahirkan dapat bertambah pula. Bertambahnya berat tubuh ibu selama hamil adalah akumulasi dari berat tubuh ibu pra konsepsi dan bertambahnya berat tubuh ibu selama kehamilan (Rosyida & Hidayatunnikmah, 2020). Tahap pertumbuhan janin di dalam kandungan merupakan bentuk dari kenaikan berat tubuh ibu selama kehamilan.…”
Section: Pembahasanunclassified
“…Selain Itu dalam pengabdian masyarakat ini juga berkesinambungan mengingat kita juga harus memantau kepatuhan Ibu dan Anak dalam mengkonsumsi PMT (Iswati et al, 2019). Dengan memperbaiki kondisi yang ada di lingkungan tersebut peneliti ingin pelakukan pendampingan dalam membuat makanan tambahan baik Itu pada Ibu dan pada bayi (Rosyida & Hidayatunnikmah, 2020).…”
Section: Pendahuluanunclassified